Analisis Butir Soal Bahasa Arab Perspektif Anderson dan Krathwohl - Zulfa, Alfiyyatuz; Zunairoh, Yuyun; Baity, Anggi Nurul (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2024)
Evaluation is an important role in education to assess the extent to which learning objectives have been achieved. In this context, the role of the teacher is crucial in designing evaluations. According to the Law of the Republic of Indonesia Year 2005 Article 10 Paragraph 1, evaluating the assessment tools that have been prepared is part of the teacher's pedagogical competence. This means that teachers must be able to design and assess evaluation tools to ensure that learning objectives are effectively achieved. In drafting test items, there are various levels of difficulty. Anderson and Krathwohl divide them into three levels: LOTS, MOTS, and HOTS. The type of research used is library research. The data source for this research is the final exam questions for the odd semester of the Arabic language subject for the 2023/2024 academic year on 7th grade in Islamic Junior High School 5 Nganjuk, East Java. The analysis method used to analyze this discussion is a qualitative analysis method using content analysis. The results of the study show that: 1) some questions still focus on LOTS and MOTS levels, with more LOTS and MOTS questions included than HOTS questions, thus requiring re-formulation. 2) From the analysis conducted, it was found that there are 25 LOTS questions, 23 MOTS questions, and 2 HOTS questions, and it was noted that the included HOTS questions lack variety.